Diesel Engine Cycle Analysis of Two Different TBC Combustion Chamber. (2016) - Gosai, D.C.; Nagarsheth, H.J.
Abstract: Efficient energy usage and energy conservation is the today's requirement for all researchers of IC engine. The usual method of producing heat from fuel is by the process of combustion, which is a chemical reaction between the fuel and oxidant. Thermodynamics is the science that deals with interaction between energy and material systems. In case of I C, engine about one-third of total energy is used as conversion of useful work. Diesel engine is operated at higher compression ratio, so low heat rejection engine is made by applying better ceramic TBC material. The concept of adiabatic engine is used to save the loss of energy and also minimize the exhaust emissions. Further efforts were made by computerized experimental work by using twin cylinder water cool constant speed diesel engine. The self-governed diesel engine combustion chamber components like piston's top surface, engine heads, valves and liners were fully coated with two different better TBC materials like MgZrO3 and YSZ. In both cases, TBC bond coat NiCAlY are used for better mechanical strength. The diesel combustion cycles analysis were carried and different combustion results displayed like, crank angle verses cylinder pressure, mass fraction, heat release and pressure volume diagram. The result indicates that, better combustion is found in MgZrO3 type ceramic TBC material diesel engine.